Translational Cancer Research (TCR) is going to publish monthly starting in September 2019! - Office, Editorial (Translational Cancer Research, 2019)
Since its launch in 2012, Translational Cancer Research (TCR) has been published bi-monthly with both online and printed copies. From year to year, the submissions to TCR has been rapidly increasing. This is a reflection of the ever-increasing recognition of TCR and continuing support by our authors. As a high-quality academic exchange platform, we would like to assist more and more clinicians and researchers in showcasing their scientific achievements. We are also committed to publishing articles quickly, allowing for impactful and potentially practice-changing articles to be available to readers soon after acceptance. Therefore, we are delighted to inform you that the TCR will be a monthly publication beginning in September 2019.